Legal Framework for Optimizing Nazhir’s Role in Waqf Asset Management for Economic and Social Development - Fauziah, Fauziah; Salamah, Ade; Lubis, Efridani; Intihani, Siti Nur; Fadillah, Syarif (Jurnal Pembaharuan Hukum, 2025)
Waqf is a recommended form of worship for Muslims because its rewards continue even after the donor (wakif) has passed away, as long as the donated assets provide ongoing benefits. In Indonesia, waqf is regulated by Law Number 41 of 2004, which emphasizes that waqf functions to realize economic potential for worship and public welfare. This highlights the importance of strengthening nadzir’s role and capacity in managing waqf assets productively. This research aims to examine nadzir’s role in managing waqf assets in Bekasi City and to identify strategies for optimizing their skills to support social and economic development. The study uses a combination of normative juridical methods, by analyzing laws and regulations, and empirical juridical methods, by collecting primary data through interviews with nadzir, wakif, the Indonesian Waqf Board (Badan Waqaf Indonesia/BWI), and the local community. The findings show that nadzir has a strategic but challenging role, as many lack adequate training and support from relevant institutions. Therefore, optimizing nadzir’s capacity through structured training and government-backed guidance is crucial. The study concludes by recommending sustainable skill development programs for nadzir to ensure waqf assets can truly contribute to community welfare.